Analysis of solar photovoltaic energy potential in Brazilian hydroelectric reservoirs through floating panels - Santos,Francielle da Rocha (2019)
Abstract Sustainability, a concept used to exploit natural resources without harming future generations, is being applied to power generation. In Brazil, the main source of electric energy comes from hydroelectric plants, due to abundant water resources. However, the implementation of these plants causes irreversible impacts on the environment and society. On the other hand, the impacts caused by photovoltaic panels are considerably smaller in the construction phase and zero in the operation phase. This article describes the impacts generated by hydroelectric power plants and gives an overview of the power generated by floating photovoltaic panels using 10% of the area of the reservoirs of the largest hydroelectric power plants in Brazil. The results demonstrate a better efficiency of the photovoltaic panels in the water, which cools them, increasing their efficiency. Furthermore, photovoltaic panel power generation amount is higher than compared the annual power generation of three out of four hydroelectric plants analyzed. In addition, adding solar energy to the reservoirs would save infrastructure costs, considering that energy can be made available through substation infrastructure and existing power transmission systems.